Atomistic studies of ductile fracture of a single crystalline cantor alloy containing a crack at cryogenic temperatures. (December 2021) - Ji, Weiming; Wu, Mao See
Graphical abstract: Highlights: Cantor alloys with an edge crack exhibit ductile failure at cryogenic temperatures. The J -integral at yield may be used as a criterion to determine the yield stress. Dislocations, twinning and cavitation contribute to crack retardation. A transition from cavitation to shear faulting occurs with increased strain. Abstract: In this paper, atomistic studies show that Cantor alloys containing a pre-existing crack under tension are ductile at cryogenic temperatures. Specifically, the effects of crack length on the mechanical properties of single-crystalline Cantor alloys under mode I loading at the temperature of 0.1 K are investigated via molecular dynamics (MD) simulations. For different initial crack lengths ranging from 25 to 45 nm, the J -integral is calculated at the critical point of dislocation emission, and the work-of-fracture is calculated at the fracture strain. The results show that the Young's modulus and yield stress decrease with the increased crack length. The J -integral is not significantly affected by the crack length, due to the fact it is governed by the length-independent unstable stacking fault energy. However, the work-of-fracture increases with increased crack length. Nucleation and growth of nanosized cavities in front of the crack tip are observed and the crack propagates through coalescence of cavities, which agrees well with previous experimental findings. As the tensile strain increases, there is a transition from cavitation to shear faulting, after which the stress-strain responses are independent of the crack length. The cavitation and shear faulting dissipate a large amount of energy needed for crack propagation, leading to ductile fracture of Cantor alloys at cryogenic temperatures.